Mitochondrial dynamics and their intracellular traffic in porcine oocytes. Issue 4 (14th September 2015) - Yamochi, T.; Hashimoto, S.; Amo, A.; Goto, H.; Yamanaka, M.; Inoue, M.; Nakaoka, Y.; Morimoto, Y.
Summary: Meiotic maturation of oocytes requires a variety of ATP-dependent reactions, such as germinal vesicle breakdown, spindle formation, and rearrangement of plasma membrane structure, which is required for fertilization. Mitochondria are accordingly expected be localized to subcellular sites of energy utilization. Although microtubule-dependent cellular traffic for mitochondria has been studied extensively in cultured neuronal (and some other somatic) cells, the molecular mechanism of their dynamics in mammalian oocytes at different stages of maturation remains obscure. The present work describes dynamic aspects of mitochondria in porcine oocytes at the germinal vesicle stage. After incubation of oocytes with MitoTracker Orange followed by centrifugation, mitochondria-enriched ooplasm was obtained using a glass needle and transferred into a recipient oocyte. The intracellular distribution of the fluorescent mitochondria was then observed over time using a laser scanning confocal microscopy equipped with an incubator. Kinetic analysis revealed that fluorescent mitochondria moved from central to subcortical areas of oocytes and were dispersed along plasma membranes. Such movement of mitochondria was inhibited by either cytochalasin B or cytochalasin D but not by colcemid, suggesting the involvement of microfilaments. This method of visualizing mitochondrial dynamics in live cells permits study of the pathophysiology of cytoskeleton-dependent intracellular traffic of mitochondria and associated energy metabolism during meiotic maturation of oocytes.